An Examination of Order Maintenance Policing by Business Improvement Districts - D'Souza, Amanda (Journal of contemporary criminal justice, 2020)
Despite their ability to improve public safety, research has often prioritized the central role of the police in order maintenance, frequently overlooking the activities of non-state organizations. The current study examines the role of one such security program, Business Improvement Districts (BIDs). Specifically, it explores how BIDs’ security teams, also known as Public Safety Officers, enforce order within their local districts. Data were collected from 76 semi-structured interviews and 171 hr of participant observations within four different BIDs in the two American cities. Findings illustrate how study participants demonstrated their use of reporting, surveillance, and other behavioral strategies to establish order and themselves as guardians within their districts. Scholars’ disproportionate focus on the work of the police downplays the importance of private organizations. This study is an exploration into a piece of this larger order maintenance network.